The Impact of the Pandemic on English Language Teaching in Inclusive Education (Research, Society and Development, 2021)
This article describes how to deal with home and remote English language teaching with special students during the COVID-19 period. Employing a primarily qualitative research approach, five parents with children diagnosed with autism spectrum disorder were interviewed online. Data were subjected to thematic analysis. The results highlight the following themes: (1) many are better than one at homeschooling during isolation; (2) struggles with the transition to cultivating new activities; (3) new social reality in preparation for the post-pandemic period; (4) all forms of home education are essential; and (5) families encouraging families in these difficult times. This article provides insights into the remote education of children with autism in the midst of the current global emergency.